Anatomy of a reindeer dissected in Copenhagen in 1672 by Niels Stensen as reported by Thomas Bartholin. I. Introduction by Troels Kardel. II. Translation by Paul Maquet - Kardel, Troels; Maquet, Paul (Rangifer, 2013)
A report by Professor Thomas Bartholin on the dissection of a reindeer performed in 1672 by his former student Niels Stensen as Royal Anatomist in Copenhagen is presented in English translation with biographical introduction and bibliographical notes. The report is most likely the first of its kind being an early contribution to comparative anatomy.